Efeito da adição de argila expandida e adições minerais na formulação de concretos estruturais leves autoadensáveis - Borja, Edilberto Vitorino de (2011)
The search for alternative materials with lower density, reduction in heat transfer and propagation of noise associated with the ease of handling and application in concrete structures, represents an enormous challenge in the formulation and knowledge of the performance of self-compacting lightweight concrete, which has technology little known nationally, and appears on the international scene as an innovative material and alternative to conventional concrete. Based on these, this study set out to study self-compacting lightweight concrete made with two distinct grades of expanded clay associated with the addition of plasticizing/superplasticizers additives and mineral additions of metakaolin and bagasse ash of sugar cane. There is also an object of study, evaluation of pozzolanic activity of mineral admixtures and their influence on the durability characteristics of concrete. The rheological, physical, mechanical and microstructural analysis in this study served as basis in the classification of concretes autoadensáveis, targeting the national technical requirements for their classification in the category autoadensável and lightweight structural. The inclusion of mineral admixtures (metakaolin and bagasse ash of sugar cane), partial replacement of cement, pozzolanic activity and demonstrated maintenance of mechanical properties through the filler effect, a reduction of up to 76% of the nitrogen gas permeability in blend with 20% bagasse ash. All concretes had rheology (cohesion and consistency) suitable for self-adensability as well as strength and density inherent structural lightweight concrete without presenting phenomena of segregation and exudation